1990
DOI: 10.1002/jobm.3620300418
|View full text |Cite
|
Sign up to set email alerts
|

Selective and rapid solubilization of the microbial membrane enzyme aldehyde dehydrogenase

Abstract: An improved solubilization procedure for the membrane-bound quinoprotein aldehyde dehydrogenase from Acetobacter rancens CCM 1774 was established. After the first solubilization of membrane enzymes by Brij 35 which provided important extraction of membrane proteins other than aldehyde dehydrogenase, the application of Trition X-100 resulted in an almost 20-fold purification of quinoprotein aldehyde dehydrogenase. The optimal solubilization was closely connected with definite detergent/protein ratios.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2008
2008

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…8,9 Polyoxyethylene (23) lauryl ether or Brij R 35 is an extensively studied nonionic surfactant and finds many applications including dissolution of polymers and extraction of proteins from membranes. 10,11 The microwave irradiation (MW) technique for chemical syntheses has been popular in recent years and there are many reports of the preparation of new materials using this technique. 12- 15 It was found that the rate of reactions and yield of product for the reactions carried out by MW irradiation is superior to the conventional heating techniques.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Polyoxyethylene (23) lauryl ether or Brij R 35 is an extensively studied nonionic surfactant and finds many applications including dissolution of polymers and extraction of proteins from membranes. 10,11 The microwave irradiation (MW) technique for chemical syntheses has been popular in recent years and there are many reports of the preparation of new materials using this technique. 12- 15 It was found that the rate of reactions and yield of product for the reactions carried out by MW irradiation is superior to the conventional heating techniques.…”
Section: Introductionmentioning
confidence: 99%